Pirólise de pequi (Caryocar Brasiliense) – avaliação do rendimento e da caracterização química da fração orgânica - Silveira , Iara Sousa (Universidade Federal do Tocantins, 2020)
Since the energy crisis of 1970 power was seen as a scarce, or at least not inexhaustible, and received a lot of investment in research and development for renewable energy alternatives. With this argument was studied pequi, which is the fruit of the native Brazilian Cerrado, for energy exploration. This study aimed to obtain the organic fraction from the application of pyrolysis process on the biomass pequi and evaluate the performance of the process pyrolysis applied to biomass pequi, levels of temperature threshold 450 º C and 550 º C, rates heating rate 10 ° C / min and 30 ° C / min and residence time of the biomass temperature level of 120 minutes and 180 minutes, characterize in terms of physicochemical fraction organic liquid obtained from the gas chromatography analysis aclopada the mass spectrometry and density analysis, and characterize the biomass applied in the process performing the following analyzes: moisture, ash, calorific value, vegetable oil extraction and TGA. In the organic fraction was obtained 42 organics different, with the highest yield equal to 37.57% (w/w) to the organic fraction under the following conditions: temperature 450° C, 30° C/min heating rate and 180 minute time reaction indicative of continuing studies for this situation great. Functional groups indicated the possibility of application the same in the following sectors: energy (oil, fatty acids and phenols) and chemical (fatty acids).